The Impact of Promotional Strategies on Customer Decisions to Save at PT Bank Sumut KCP USU - Sebayang, Immanuel Edy Suranta (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research examines how PT Bank Sumut KCP USU's promotion strategy affects customers' decisions to save. The study's population consists of 12,650 customers of PT Bank Sumut KCP USU. Using the Slovin formula, 100 participants were selected for the sample. The data analysis approach employed multiple linear regression analysis, including statistical tests (F, T, and determination coefficient) and tests for classical assumptions (normality, multicollinearity, autocorrelation, and heteroscedasticity). The normalcy test using Kolmogorov-Smirnov found that the data distribution is normal. There were no signs of heteroscedasticity, autocorrelation, or multicollinearity. The regression analysis revealed a partially positive and significant influence from advertising and direct marketing, and a partially positive but non-significant effect from sales promotion, public relations, and personal sales. An R-squared value of 0.488 indicates that the independent variables explain 48.8% of the variance in the dependent variable, with the remaining 51.2% attributed to factors not included in the regression model